Analisis Inovasi Produk, Kuantitas Pelayanan, Fasilitas Dan Harga Terhadap Keputusan Penggunaan Jasa Pada Make Up Artist Mey Slowis Cikampak - Dela Kartika (Jurnal Manajemen Akuntansi (JUMSI), 2021)
Customer satisfaction is an element in achieving corporate goals and maintaining income in a company. Various factors to obtain customer satisfaction, and in the service required quality of service to obtain customer satisfaction. In this study describes how the analysis of product innovation, quantity of services, facilities and prices to the decision of the use of services in make up artist Mey slowis cikampak. The results in this study obtained that the partial variable of Product Innovation has a positive and significant effect on purchasing decisions, it is seen from the value of thitung for product innovation is thitung 2.569 > ttable 1.697. Partially variable quantity of Service has a positive and significant effect on purchasing decisions, it is seen from the value of Thitung for quantity of Service is thitung 1.741> ttable 1.697, with a significant value of 0.026 < 0.05. Then it can be concluded that Ho is rejected and Ha is accepted. Partially variable facility positive and significant effect on purchasing decisions, it is seen from the value of Thitung for facilities (X3) is thitung 1.823> ttable 1.697, with a significant value of 0.010< 0.05. Partially variable price has a positive and significant effect on purchasing decisions, it is seen from the value of thitung for the price is thitung 2.252> ttable 1.697, with a significant value of 0.033< 0.05.